Blurring the Distinction Between Empirical and Normative Legitimacy? A Methodological Commentary on ‘Police Legitimacy and Citizen Cooperation in China’ - Jackson, Jonathan (Asian journal of criminology, 2019)
In a fascinating study into the nature of police legitimacy in Southern China, Sun et al. (2018) present evidence that what researchers have previously been treated as possible sources of legitimacy—public perceptions of police conduct defined along the lines of procedural justice, distributive justice, effectiveness and lawfulness—are in fact constituent components of legitimacy. In this methodological commentary, we argue that the empirical strategy used to reach this conclusion is not fit for purpose because both conceptual stances—possible sources of legitimacy or constituent components of legitimacy—are consistent with the same fitted statistical model. Analysing nationally representative data from 30 countries across Europe and beyond, we also show that erroneous support for the approach to measurement is likely to be found wherever one looks. To be sensitive to cultural context means using a methodology that does not impose the preconditions of legitimacy, and we counsel against a trend starting in international criminology that does precisely the opposite.